2022
DOI: 10.1111/acel.13543
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for advanced glycation end products aggravates cognitive deficits in type 2 diabetes through binding of C‐terminal AAs 2‐5 to mitogen‐activated protein kinase kinase 3 (MKK3) and facilitation of MEKK3‐MKK3‐p38 module assembly

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 74 publications
5
28
0
Order By: Relevance
“…This is supported by our study that mutation of RAGE AAs 362-367 prevents the interaction of RAGE with RIPK1 and blocking activation of RIPK1 and its downstream in ammation-related signaling pathway in db/db mice. This is an important complement to our previous ndings, which reported that the binding of RAGE to MKK3 is an essential event for activation of the p38MAPK signal pathway in neuron under high-glucose conditions [21]. In the present study, the results show that the interaction between RAGE and RIPK1 induces RIPK1 phosphorylation and NLRP3 in ammasome activation in microglia.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This is supported by our study that mutation of RAGE AAs 362-367 prevents the interaction of RAGE with RIPK1 and blocking activation of RIPK1 and its downstream in ammation-related signaling pathway in db/db mice. This is an important complement to our previous ndings, which reported that the binding of RAGE to MKK3 is an essential event for activation of the p38MAPK signal pathway in neuron under high-glucose conditions [21]. In the present study, the results show that the interaction between RAGE and RIPK1 induces RIPK1 phosphorylation and NLRP3 in ammasome activation in microglia.…”
Section: Discussionsupporting
confidence: 88%
“…Given the crucial role of RAGE in hyperglycemia-induced neuroin ammation, we initially investigated the RAGE-interacting proteins in hippocampus of db/db mice through liquid chromatograph-mass spectrometer (LC-MS) analysis. We found that the abundance of proteins associated with the mitogenactivated protein kinase (MAPK) signaling pathway was signi cantly increased in db/db mice [21]. It was worth mentioning that the protein abundance of RIPK1, which can induce neurodegenerative diseases by enhancing the in ammatory response, was found to be signi cantly elevated in db/db mice (Fig.…”
Section: Restults Rage Interacts With Ripk1 and Enhances Its Phosphor...mentioning
confidence: 76%
See 2 more Smart Citations
“…Given the crucial role of RAGE in hyperglycemia‐induced neuroinflammation, we investigated RAGE‐interacting proteins in the hippocampus of db/db mice through liquid chromatograph–mass spectrometry (LC–MS) analysis. We found a significant increase in the abundance of proteins associated with the mitogen‐activated protein kinase (MAPK) signaling pathway in db/db mice 25 . In particular, the abundance of RIPK1 protein, which can induce neurodegenerative disease by enhancing the inflammatory response, was significantly elevated in db/db mice (Figure 1A1,A2).…”
Section: Resultsmentioning
confidence: 89%